مقصد التعارف وأثره في القانون الدولي الإسلامي: The Purpose of Acquaintance among nations and its impact on Islamic International Law - Farida Hayed - حايـد, فريـدة (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2018)
يهدف البحث إلى بيان أثر التعارف بين الشعوب والأمم، بوصفه مقصداً يتصل بالقيم الناظمة لبناء العلاقات الدولية في الإسلام؛ والإسهام في تأصيل فقه العالم والإنسانية جمعاء، في ظل اختلاف المصالح والحاجات. ويبين البحث ضرورة بناء مقصد التعارُف على قيم الحضارة ومعاني الإسلام السامية، التي من بينها فقه التعارف، وما يقوم عليه من أُسس تُعنى بالوحدة الإنسانية في ظل الاختلاف والتنوُّع. Islam considers acquaintance among nations as an essential purpose related to values of constructing international relations. This study deals with the impact of this purpose on the Islamic international law, in order to contribute to the building of foundations for the jurisprudence of the world and humanity, taking into consideration the conflicting interests and needs. The study explains the need to build the purpose of acquaintance among nations on values of civilization prescribed by Islamic principles including the unity of humanity while respecting diversity and differences.